Polymer fuel cells. Part I. Principle of operation, types and methods of investigations - Malinowski, M.; Iwan, A. (Polimery, 2014)
The paper is a literature review concerning polymer fuel cells. In the first part the structure, principle of operation and types of fuel cells (FC) are discussed. In-situ techniques used for evaluation of FC parameters in a single cell or assembled stacks, such as current-voltage characteristics (polarization curve), current interruption method, cyclic and linear sweep voltammetry, electrochemical impedance spectroscopy, cathode discharge and current mapping are presented. The mechanism of operation and functions of fuel cell components are discussed in details using the example of PEMFC (Polymer Electrolyte Membrane or Proton Exchange Membrane fuel cells). Two types of PEMFC are distinguished, i.e. HT (High Temperature) and LT (Low Temperature) indicating the advantages of high-temperature operation. The second part of this review is related to different kinds of polymers used in fuel cells and describes practical applications of polymer fuel cells.